EFFECT OF MgO NANOPARTICULE ADDITIVES ON PERFORMANCE AND EXHAUST EMMISSIONS OF DIESEL FUELLED COMPRESSION IGNITION ENGINE - ÖZGÜR, Tayfun; TOSUN, Erdi; ÖZGÜR, Ceyla; TÜCCAR, Gökhan; AYDIN, Kadir (MATTER: International Journal of Science and Technology, 2017)
Nowadays energy requirements have been rapidly growing due to increasing population and industrialization. Diesel engines have a huge role in environmental pollution. Harmful gas emissions increase along with energy consumption, therefore, new ways to restrict harmful gases and to take precautions are sought. In this study, MgO nanoparticle additive with extra oxygen content were used in diesel fuel in compression ignition engines, in order to monitor fuel properties, performance and emission values. Dosage of additive into diesel fuel were 25, 50 and 100 ppm and the optimum dosage of additives was determined in relation to decrease of NOx and CO emissions.